PENGEMBANGAN BAHAN AJAR BERBASIS E-BOOKS TERHADAP HASIL BELAJAR IPA MATERI PERUBAHAN WUJUD BENDA SISWA DI SEKOLAH DASAR - Andrianti, Tetie; Widiyono, Aan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The limited interactive teaching materials that are in accordance with the characteristics of grade 3 elementary school students are often an obstacle in science learning, especially in the material of changes in the state of objects. This study aims to develop and determine the feasibility of interactive e-book-based teaching materials on the material for grade 3 students of SDN 1 Guyangan. The research method used is Research and Development (R&D) by adapting the ADDIE model. The stages include analyzing the needs of students and teachers through interviews and questionnaires; designing e-books with attractive multimedia elements; developing products using appropriate software; limited implementation in the classroom to measure effectiveness, involvement, and ease of use through observation and questionnaires; and formative and summative evaluations based on expert validation results and user responses. The validation results show that the developed e-book is very feasible, with a score from material experts of 93.75% and from media experts of 95.3%. The responses of teachers and students during implementation also showed that this e-book is very practical, effective, and easy to use, thus increasing learning engagement. Thus, the interactive e-book developed is declared very feasible and practical to support and improve the quality of science learning on the material of changes in the state of objects in elementary schools. ABSTRAKKeterbatasan bahan ajar yang interaktif dan sesuai dengan karakteristik siswa kelas 3 SD seringkali menjadi kendala dalam pembelajaran IPA, khususnya pada materi perubahan wujud benda. Penelitian ini bertujuan untuk mengembangkan dan mengetahui kelayakan bahan ajar berbasis e-book interaktif pada materi tersebut untuk siswa kelas 3 SDN 1 Guyangan. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan mengadaptasi model ADDIE. Tahapannya meliputi analisis kebutuhan siswa dan guru melalui wawancara dan angket; perancangan e-book dengan elemen multimedia yang menarik; pengembangan produk menggunakan perangkat lunak yang sesuai; implementasi terbatas di kelas untuk mengukur efektivitas, keterlibatan, dan kemudahan penggunaan melalui observasi dan angket; serta evaluasi formatif dan sumatif berdasarkan hasil validasi ahli dan respon pengguna. Hasil validasi menunjukkan e-book yang dikembangkan sangat layak, dengan skor dari ahli materi sebesar 93,75% dan dari ahli media sebesar 95,3%. Respon guru dan siswa selama implementasi juga menunjukkan bahwa e-book ini sangat praktis, efektif, dan mudah digunakan sehingga meningkatkan keterlibatan belajar. Dengan demikian, e-book interaktif yang dikembangkan ini dinyatakan sangat layak dan praktis untuk mendukung serta meningkatkan kualitas pembelajaran IPA materi perubahan wujud benda di sekolah dasar.